COST STUDY IN THE SPECIAL CARE SECTOR OF THE HOSPITAL DR. JOSÉ PENNA FROM BAHÍA BLANCA (Costos y Gestión, 2021)
n Argentina the health organization sectors had been experienced a vast growth of expenses, and the lack of information technology systems, in the majority of them, make the organizations incapable to offer an integrated and complete details of cost estimation as a management tool for decision making. This situation is even more visible in the health public sub-sector which is the one that covers the people without health insurance (36% of the population). Nevertheless, this circumstance does not mean that the national government has to ignore the economic conditions and the possibility to make better use of its own resources. In this context, the objective of the work will be calculate and analyze the costs incurred by the «Special Care» inpatient sector of the Bahía Blanca «Dr. José Penna Hospital» and estimate the occupied bed cost per-day.The study will apply the concepts given by the «Teoría General del Costo» and it will adopt the full cost model. It starts with the description of the hospitalization process and the distribution of each part of that process showing the linkages between the actions, the results, and the factors used. Then, it reveals the sector’s production information and the factors that had been used. As a result, the fixed unit cost per patient-day at March 2017 values is $2,634, being the human resources the factor with the greatest incidence (90% of that total ). Finally, when a deficit is observed in the information about the used of variable factors per patient, it is necessary to analyze its usefulness and an improvement proposal should be presented.As a conclusion, the importance of the application of this cost estimates in the health sectors is crucial as a fundamental tool for management and decision making.
Keywords: Special Cares; Per patient-day unit cost; Occupied bed per-day unit cost; Full cost Health cost